2000
DOI: 10.7863/jum.2000.19.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasonography of distal ureteral calculi: comparison with intravenous urography.

Abstract: In a prospective fashion, transrectal ultrasonography and intravenous urography were performed in 48 patients with distal ureteral calculi. We compared the ability of the two modalities to detect calculus and to determine the size of the calculus, the degree of obstruction, and the degree of hydroureter. In 11 cases (23%), the calculus was not seen at intravenous urography, while transrectal ultrasonography detected calculus in each patient. In 37 cases in which calculi were detected by both modalities, the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…However, when filled with fluid, as in hydroureter, or with a high-density substance such as a stone or stent, it becomes echovisible. In fact, transrectal ultrasound is very sensitive for identification of distal ureteral stones [22]. In our patient, the ureter was visible as a result of the plastic stent that provided a ªbrightº plastic-to-water echo interface, allowing us to find the adjacent tumor deposit.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, when filled with fluid, as in hydroureter, or with a high-density substance such as a stone or stent, it becomes echovisible. In fact, transrectal ultrasound is very sensitive for identification of distal ureteral stones [22]. In our patient, the ureter was visible as a result of the plastic stent that provided a ªbrightº plastic-to-water echo interface, allowing us to find the adjacent tumor deposit.…”
Section: Discussionmentioning
confidence: 69%
“…At 17 cm from the anus, an ill-defined area of mixed echotextures was seen to the right of the rectosigmoid junction. Thereafter, a linear-array echo endoscope (GFUC 140P; Olympus) was introduced and, in the presence of a cytopathologist, three FNA samples were obtained from the suspicious area with a 22 Endoscopic ultrasound (EUS) is a standard tool for imaging the gastrointestinal tract and adjacent structures. EUS-guided fineneedle aspiration (FNA) allows the endosonographer easy access to these structures for both diagnostic and therapeutic purposes.…”
Section: Case Reportmentioning
confidence: 99%
“…The use of pulsed and color Doppler US has enabled the evaluation of the function and obstruction of both kidney and ureter [ 9 ]. It was previously suggested that the presence of a ureteral jet could be used to exclude complete ureteral obstruction, and the complete absence of a jet is symptomatic of a high-grade obstruction caused by ureteral calculi in humans [ 3 8 11 14 21 25 36 38 42 ]. Complete obstruction can be reliably ascertained by the absence of a ureteral jet on the suspected side of the obstruction with extremely high sensitivity and specificity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of jet could be used to exclude ureteric obstruction. The complete absence of jet or a continuous low-level waveform is diagnostic for high-grade obstruction from ureteric calculi (Abulafia et al, 1997;Burge et al, 1991;Catalano et al, 1998;Elejalde & de Elejalde, 1983;Laing et al, 1994;Tal et al, 1994;Timor-Tritsch et al, 1997;Wu et al, 1995;Yoon et al, 2000).The difference in jet velocity has been used to study the effect of drug treatment on benign prostatic hyperplasia (Sperandeo et al, 1994(Sperandeo et al, , 1996 and to study the physiology of the kidney and ureter, includingthe glomerular filtration rate (Blomley et al, 1997;Burke & Washowich, 1998;Chiu et al, 1999;Han et al, 1996Han et al, , 1997Patel et al, 1996;Summers et al, 1992;Wachsberg, 1998)…”
Section: Clinical Implication Of Ureteric Jetmentioning
confidence: 99%